Potential of Preoperative Testosterone Stimulation Therapy to Reduce Complication in Hypospadias Repair: A Systematic Review and Meta-Analysis - Munawwir, Abdul; Mustamar, Fikri Akbar; Palinrungi, Muhammad Asykar; Aristo, Aristo (Brawijaya Journal of Urology, 2025)
Introduction. The pre-operative hormone stimulation is recommended for hypospadias patients, especially those with small penis, to improve the results and outcomes of hypospadias repair. We conducted a systematic review and meta-analysis to evaluate the effectiveness of pre-operative testosterone stimulations before hypospadias repair. Methods. We performed a comprehensive search for relevant studies from PubMed, Medline, Cochrane, Proquest, and Embase from August 2000 until August 2023 . The phrases "hypospadias" and "testosterone treatment" were utilized. Only studies focusing on patients diagnosed with hypospadias were considered. This analysis exclusively included English-language papers, randomized control trials, cohort studies, and case-control studies. Case studies without comparable groups were excluded. Editorials, comments, and review articles were excluded from the study. We used the PRISMA guidelines for this systematic review and meta-analysis report. RevMan version 5.4.1 was used to analyze and evaluate the data. Results. A total of 832 patients undergoing urethroplasty were evaluated in 7 studies. A total of 372 patients were categorized into the intervention group, which received testosterone hormone therapy (parenteral, intramuscular, and topical). Patients who receive preoperative testosterone therapy have a 0.68 reduced risk of complications rate compared to those who did not (P = 0.03, I2 = 28%, CI: 0.68, OR: 0.48 - 0.96), reduced meatal stenosis (P = 0.04, OR: 0.66, 95% CI: 0.44 - 0.98, I2 = 28), reduced the risk of postoperative glans dehiscence (P = 0.0004, OR: 0.46, 95% CI (0.30-0.71), I2 = 57%), and reduced risk of fistula urethrocutaneous (P = 0.03, OR: 0.58, 95% CI: 0.36 - 0.94, I2 = 22%). Conclusion. Pre-operative testosterone stimulation can improve surgical outcomes. Complication rates, such as meatal stenosis, glans dehiscence, and fistula, showed a significant effect in patients who intervened with testosterone stimulation pre-hypospadias repair. Keywords: hypospadia, improve, outcome, repair, testosterone